Pengaruh Keterampilan Kerja dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan pada UMKM Batik Lestari Plupuh, Sragen - Rendy Josua Titirloloby; Sutarno (Teewan Journal Solutions, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting Indonesia’s economy. One of the MSMEs facing employee productivity problems is Batik Lestari Plupuh, Sragen. This study aims to analyze the influence of work skills and work motivation on employee productivity. This research employed a quantitative method with a survey approach. The population consisted of all 40 employees of Batik Lestari, who were entirely taken as the sample using a saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression, t-test, F-test, and coefficient of determination (R²). The t-test results showed that work skills (X1) significantly affect employee productivity (Y), and work motivation (X2) also has a significant effect on employee productivity. The F-test resulted in an F-value of 28.496 with a significance level of 0.000 < 0.05, indicating that the model is feasible. The coefficient of determination (Adjusted R²) was 0.585 or 58.5%, meaning that work skills and motivation contributed 58.5% to employee productivity, while the remaining 41.5% was influenced by other factors outside the research model.